OUTCOMES OF PRP INJECTION THERAPY IN SUBACROMIAL SPACE IN PARTIAL TEARS OF ROTATOR CUFF - HARMANPREET SINGH; SAHIL VERMA; KSHITIJ MEHTA; DALJINDER SINGH; DHARMINDER SINGH; GIRISH SAHNI; SIMRAN (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The aim of the study was to record therapy in the subacromial area in cases of partial rotator cuff (RC) tears on controlling pain and improving shoulder mobility and performing daily activities with ease. Methods: The study was conducted in the Orthopedics branch of Government Medical College and Rajindra Hospital Patiala on a total of 50 patients (aged more than 20 years) who presented in the emergency and Outpatient Department with symptoms of anterolateral shoulder pain and decreased range of motion at shoulder joint, who had not responded to conservative management and physiotherapy measures for consecutive 3 months. The patients were subjected to magnetic resonance imaging of the affected shoulder and those who showed partial cuff tears were considered for the study. Every consenting patient was given a PRP injection by posterior approach into the subacromial space. Patients were then followed up subsequently after 1 month, 6 months, 12 months, and 24 months for resolution of symptoms and improved painless activities at the shoulder. The outcome was assessed based on Visual Analog Scale (VAS) system and constant shoulder scoring system. Results: Comparison of the patients before and after injection therapy revealed a significant difference in VAS and constant shoulder scale at all the follow-up times with maximum improvement at the longest follow-up period. Conclusion: Injection of PRP in subacromial space was found safe and effective in enhancing overall life quality with the betterment of symptoms in patients with anterolateral shoulder pain, and thus, improving efficiency of work, shoulder functioning in patients having partial RC tears irrespective of its cause with its beneficial effects more at long term.